Dampak Kebijakan Uang Muka pada Pertumbuhan Kredit Kendaraan Bermotor Perbankan - Ardini, Dita; Soesilo, Nining I (Jurnal Kebijakan Ekonomi, 2023)
Macroprudential policies are increasingly being used in various countries after the global financial crisis in 2008. One of the macroprudential policies in Indonesia is the motor vehicle loan down payment policy. This study discusses the impact of the down payment policy on the growth of banking motor vehicle loans in Q1 2011 to Q4 2019. Using the fixed effect model method, the study was conducted on all banks that provided motor vehicle loans during the study period. The results indicate that down payment policy has significant impact on the growth of banking motor vehicle loans. The growth of motor vehicle loans decreases when the down payment policy is tightened and increases when the down payment policy is eased.